A Case Study Of IOI Plantations - Hasan, Md. Mahmud (2008)
This case study diagnoses IOI internal and external environments of the company and benchmarking IOI performance versus its industry competitors. In addition, this study also seeks to evaluate business strategies that IOI employs and outline strategic plans that are required to reposition itself in strive to maintain competitiveness, sustaining growth and thus generating greater profits.